THEORY AND EFFECTS OF FOREIGN DIRECT INVESTMENTS - Синиша Куртеш, M.Sc. (Acta Economica, 2008)
International capital flow, meaning import, export and capital transference is becoming more and more topical issue related to theoretic-practical and economic-political problems in all countries regardless their level of economic development. It is not just about capital movements from developed countries to undeveloped, but it is also about capital movements between developed countries. Problems concerning import and export of capital are very complex and they ask for deep theoretical and practical analysis, most of all analysis concerning size, structure and types of capital movements. Deep theoretical and practical analysis of international capital movement presumes retrospection on former thoughts and critical scientific analysis of this phenomenon.